Correlation between post-injury mental health symptoms and rehabilitation adherence in collegiate athletes - Torres, L; Gardin, F; Davis, S; Shotwell, C. (The Sport Journal, 2025)
Purpose: To explore the correlation between post-injury mental health symptoms and rehabilitation adherence in collegiate athletes to gain knowledge that would improve rehabilitative recommendations.